2020
DOI: 10.3389/fbioe.2020.00753
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the Organic and Inorganic Composition of Anabolic Bone Enhances Human Mesenchymal Stem Cell Osteoinduction and Scaffold Mechanical Properties

Abstract: Engineered bone graft designs have been largely inspired by adult bone despite functionally significant differences from the composition of anabolic bone in both the mineralized and non-mineralized fractions. Specifically, anabolic bone contains hydroxyapatite with ionic substitutions that facilitate bone turnover and relatively rare collagens type VI and XII that are important for normal bone development. In this work, human mesenchymal stem cells (hMSCs) were cultured in lyophilized collagen type I scaffolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…From a histological standpoint, bone tissue is a natural combination of bioceramic and polymer phases, principally apatite and collagen [ 70 ]. Therefore, nanocomposite polymer hybrid scaffolds have tremendous potential for bone tissue engineering [ 71 , 72 ]. Porous 3D polymeric Nanocomposite scaffolds have been repeatedly reported to provide a suitable matrix for connecting and expanding different cell types [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a histological standpoint, bone tissue is a natural combination of bioceramic and polymer phases, principally apatite and collagen [ 70 ]. Therefore, nanocomposite polymer hybrid scaffolds have tremendous potential for bone tissue engineering [ 71 , 72 ]. Porous 3D polymeric Nanocomposite scaffolds have been repeatedly reported to provide a suitable matrix for connecting and expanding different cell types [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…[69] For this reason, we employed a freeze-drying technique while employing BDDGE as crosslinking strategy to produce bovine collagen type I-based interconnected porous structures with controlled and reproducible porosity and fiber organization, resulting in a tunable system for 3D mechanical studies. [50,70,71] In a native tissue context, cells are exposed to a variety of mechanical stimuli including hydrostatic pressure, shear, compression, and tensile force. [72] For this reason, soft biological tissues can be described as viscoelastic materials.…”
Section: Discussionmentioning
confidence: 99%
“…[ 69 ] For this reason, we employed a freeze‐drying technique while employing BDDGE as crosslinking strategy to produce bovine collagen type I‐based interconnected porous structures with controlled and reproducible porosity and fiber organization, resulting in a tunable system for 3D mechanical studies. [ 50,70,71 ]…”
Section: Discussionmentioning
confidence: 99%
“…A few recent research works based on milliscale bioreactors have demonstrated that the combined effect of perfusion and anabolic drugs (e.g., 2-chloro-5-nitrobenzanilide, a PPARγ inhibitor (GW9662), hydrogen sulphide, parathyroid hormone) can enhance collagen deposition and bone mineralization ( Grant et al, 2016 ; Liu et al, 2018 ; Gambari et al, 2019 ; Mondragon et al, 2020 ; Liu et al, 2021 ). Mondragon et al showed that perfused cultures of MSCs on lyophilized bovine collagen type I scaffolds upon which Mg-doped HA nanocrystals nucleated during collagen fibrils self-assembly and treated with GW9662, led to an increased scaffold mineral density and compressive modulus ( Mondragon et al, 2020 ). Contrary to milliscale, at the microscale this topic is completely unexplored.…”
Section: Perfused Bioreactors For Drug Screening Of Anabolic and Anti-catabolic Drugsmentioning
confidence: 99%